Violence and Resistance Related to Drug Micro-Trafficking in Greater San Miguel de Tucumán, Argentina: 2015–2022 - Wolters Albarracín, Wladimir Alejandro (2026)
This article explores the territorial concentration of intentional homicides, armed robberies, and police proceedings for microtrafficking of drugs in Greater San Miguel de Tucumán, Argentina; the place occupied by working-class neighborhoods; and the community resistance that emerged between 2015 and 2022. Information from the National Criminal Information System reveals that, although homicides were concentrated in low-income neighborhoods —due to structural factors and violence— robberies and microtrafficking proceedings have a different distribution, with a higher incidence in other urban areas. However, at the political and symbolic level, the commission of any crime is associated with these neighborhoods and their residents. Meanwhile, community organizations seek to contain microtrafficking through prevention and reduction of addiction among young people, and with measures to counteract stigmatizing discourses that come from outside.